Environmental issues and researches in India : Professor L.N. Vyas commemoration volume - Vyas, L. N., 1930-; Agarwal, S. K. 1943-; Garg, R. K. 1946- (Udaipur : Himanshu Publications, 1988)
Festschrift honoring L.N. Vyas, b. 1930, Indian botanist and ecologist.
Includes bibliographical references.
Al Amin
Keywords: Vyas, L. N., -- 1930-; Ecology -- India; Pollution -- India